Balancing Pluralism and Legal Certainty in Ijtihād through The Theories of Al-Mushawwibah and Al-Mukhaththiah - Syahrul Anwar (Asy-Syari'ah, 2023)
The formulation of Islamic legal norms (fiqh) based on zhanni (speculative) evidence often leads to divergent interpretations among mujtahid scholars. These differences can confuse within the Muslim community regarding which legal opinion should be followed. This study aims to analyse the theoretical framework of al-mushawwibah and al-mukhaththiah within the discipline of ushul al-fiqh, particularly in the context of determining legal rulings derived from zhanni sources. Employing a qualitative descriptive approach and library research method, the study examines selected verses of the Qur’an, Prophetic traditions, and the classical as well as contemporary juristic opinions. The findings reveal that the al-mushawwibah theory affirms the validity of multiple legal conclusions as long as they are grounded in sound ijtihadic methodology. At the same time, al-Mukhaththiah asserts that only one ruling can be deemed correct, though other attempts still merit reward. The novelty of this research lies in its contextual application of classical epistemological theories to contemporary fiqh disputes, such as the differing opinions on whether bank interest constitutes riba. These insights contribute to the reinforcement of legal pluralism and encourage a moderate approach in navigating diverse ijtihad-based rulings within Islamic law.